2018
DOI: 10.4012/dmj.2017-339
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mold-enclosed shear bond strength between zirconia core and porcelain veneer

Abstract: This study aimed to evaluate the mold-enclosed shear bond strength (ME-SBS) of zirconia to veneering porcelain with different surface treatments. Colored or uncolored zirconia coupons were either highly polished or airborne-particle abraded. The specimens were divided into groups with/without application of liner. Veneering porcelain was fired into an alumina ring mold on the zirconia coupons. The assembled specimens were subjected to the ME-SBS test. The mean ME-SBS for groups ranged from 7-10 MPa with no sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Ebadian et al [ 17 ] showed that coloring of zirconia specimens significantly decreased the biaxial strength of zirconia to pressed porcelain through slow tempering. Song et al [ 26 ] stated that sandblasting with 110 μ m alumina particles and 0.4 MPa pressure and coloring had no significant effect on SBS of zirconia to pressed porcelain in comparison with the control group. This difference may be due to the fact that they did not perform thermocycling in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Ebadian et al [ 17 ] showed that coloring of zirconia specimens significantly decreased the biaxial strength of zirconia to pressed porcelain through slow tempering. Song et al [ 26 ] stated that sandblasting with 110 μ m alumina particles and 0.4 MPa pressure and coloring had no significant effect on SBS of zirconia to pressed porcelain in comparison with the control group. This difference may be due to the fact that they did not perform thermocycling in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Given that interfacial chemistry and related interfacial morphologies dominate the ceramic-ceramic bonding [24][25][26], in addition to interfacial morphologies, the formation of chemical bonding should play the indispensable role in the interfacial bond. In this study, the 5-day specimen had the greater Si content and penetration depth from the results of SNMS and SEM/mapping; however, its bond strength was the least among the treated groups.…”
Section: Discussionmentioning
confidence: 99%
“…[58,59] In contrast, MgO-ZrO 2 can endure higher temperatures up to 800 C, but crystalline phase degradation would occur when treated over 1200 C, thus decreasing the mechanical properties of the material. [60] As for CeO 2 -ZrO 2 , it has a high fracture toughness and good resistance to low-temperature hydrothermal aging, but its hardness and strength are lower than that of 3Y-TZP. [43,61,62] The mechanical properties and high temperature stability of ZrO 2 ceramics can be further improved by doping various stabilizers.…”
Section: Effects Of Phase Stabilizers On Zro 2 Ceramic Fracture Tough...mentioning
confidence: 99%